Marriage an orthodox perspective - Meyendorff, John 1926-1992 (St. Vladimir's Seminary Pr., 1984)
This study on Christian marriage is a valuable resource for anyone seeking to understand the Orthodox perspective on marriage. The author examines marriage in the Church from the contexts of Judaism and the New Testament, the early church and Roman law, sacramental life, and contemporary society. Specific issues discussed include: second marriages, "mixed" marriages, divorce, abortion, family planning and responsible parenthood, married clergy, celibacy, and the monastic life. Includes text of the Orthodox marriage service.